KEPUTUSAN MEMILIH PROGRAM STUDI PENDIDIKAN EKONOMI-TATA NIAGA FKIP-UNIS TANGERANG - Adila Pebria Sari (Journal of Business Education and Social, 2020)
This study aims to determine the effect of the cost of education, the involvement of parents, peers and work opportunities on the decision to choose an economic-commerce education study program at UNIS Tangerang, both partially and simultaneously. This research uses quantitative multiple regression method, with a sample of 114 students FKIP Economic Education-Commerce. The sampling technique used was proportionate random sampling using a questionnaire method. The results showed that between the variable costs of education, the involvement of parents, peers and work opportunities, there was one variable that showed a significantly positive result, namely the peer variable. That is, the higher the peer variable, the decision to choose a study program will increasingly increase in the FKIP Economic Education-Commerce at UNIS Tangerang.Keywords: Education Costs, Parental Involvement, Peers, Job Opportunities, and Decisions to Choose Study Programs.